2020
DOI: 10.1021/acs.estlett.0c00748
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Warming Decreases Redox Capacity of Soil Organic Matter

Abstract: Globally rising temperatures increase microbial activity, accelerating decomposition of soil organic matter (SOM). SOM has numerous functional capabilities, of which the capacity to engage in reduction–oxidation reactions (or redox capacity) affects nearly all soil biogeochemical processes. How warming-induced microbial decomposition affects the redox capacity of SOM and its functional role in biogeochemical processes is largely unknown. We examined the impact of 15 years of in situ soil warming on the redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Based on the O/C ratio and H/C ratio, all compounds detected were classified into several major biochemical classes (Table S3, SI). , Duplicates of the original DOM sample showed a good reproducibility of the FT-ICR-MS analysis (Figure S2, SI). We further conducted Pearson’s correlation analysis on the relative intensities of all molecules found in duplicate samples of the original DOM, which also showed a high reproducibility ( r = 0.951, p < 0.001).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Based on the O/C ratio and H/C ratio, all compounds detected were classified into several major biochemical classes (Table S3, SI). , Duplicates of the original DOM sample showed a good reproducibility of the FT-ICR-MS analysis (Figure S2, SI). We further conducted Pearson’s correlation analysis on the relative intensities of all molecules found in duplicate samples of the original DOM, which also showed a high reproducibility ( r = 0.951, p < 0.001).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…1-3 and Fig. 2) (Bai et al 2020;LaCroix et al 2021). For instance, the quinone can accept electrons with the formation of hydroquinone, thus causing oxidation (Eq.…”
Section: Humusmentioning
confidence: 99%
“…Second, the addition of carbon into the soil has been widely conducted as a potential method for fertility enhancement, environmental remediation, and carbon sequestration, leading to the increased organic carbon content in the soil. Notably, this newly added carbon could have different properties compared to the indigenous organic carbon owing to its formation process and aging impact (LaCroix et al 2021;Wang et al 2020c). Thus, it is vital to consider the unintended consequence and potential risk of adding carbon to the soil in future studies, including both the direct mobilization of PTEs and the indirect transformation with the soil moieties.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large proportion of P bound to iron (Fe) oxides (Borch & Fendorf, 2007) could be released following Fe reduction due to redox fluctuations in humid tropical soils (Chacón et al, 2006; Gross et al, 2020; Peretyazhko & Sposito, 2005). It has been recently found that warming may change microbial metabolism and thus soil redox conditions (LaCroix et al, 2021), which could potentially affect the conversion of Fe‐bound P. However, no published study has assessed these P conversion processes under warming to determine plant P demand status, although P resorption is a crucial strategy for plants and redox fluctuations often occur in P‐deficient and humid forests.…”
Section: Introductionmentioning
confidence: 99%